Synthetic tools for studying the chemical biology of InsP8 - Riley, A; Wang, H; Shears, S; Potter, BVL (Royal Society of Chemistry, 2015)
To synthesise stabilised mimics of InsP8, the most phosphorylated inositol phosphate signalling molecule in Nature, we replaced its two diphosphate (PP) groups with either phosphonoacetate (PA) or methylenebisphosphonate (PCP) groups. Utility of the PA and PCP analogues was verified by structural and biochemical analyses of their interactions with enzymes of InsP8 metabolism.